Development of Compact Pulse Generator with Adjustable Pulse Width for Pulse Electric Field Treatment Technology - Nur Faizal Kasri; Mohamed Afendi Mohamed Piah (Institute of Advanced Engineering and Science, 2018)
The pulse generator which has been implemented in the pulse electric field (PEF) treatment system for food processing is worth to be highlighted and improved. It is parallel with the advancement in semiconductor technology, which offers robust and accurate devices. This research is an effort to produce a low cost, compact and reliable pulse generator as well as equipped with a pulse width modulation (PWM) method for wide selection of frequency and duty cycle. The result shows that the simulation process has proven the theoretical concept to be right and yields the desired outcome based on the designed values. Then, the actual printed circuit board (PCB) has been fabricated to obtain practical results which intended to be compared with the simulation outcomes. Concerning the frequency and its duty cycle, both parameters can be altered without affecting each other. It means by changing the frequency, duty cycle remains the same and vice versa. Thus, this proposed pulse generator achieves its objective and fits to be implemented in PEF treatment technology. It also can replace the conventional pulse forming network (PFN) which is bulky and costly.